Training nursing students' communication skills with online video peer assessment. (June 2016) - Lai, Chin-Yuan
Abstract: Communication is an important skill which nursing students must master in order to be effective in their career. One of the purposes of this study was to implement an online video peer assessment system to scaffold their communication skills. The other purpose was to examine the effects and validity of the peer assessment. Fifty nursing students enrolled in a psychiatric nursing course in Taiwan participated in the study. The experiment contained two rounds of peer assessments. In each round, the students had a therapeutic consultation with a simulated patient. It was recorded and uploaded on a YouTube platform which we designed to keep a log of viewing, rating and feedback from their peers. The peer assessment process was synchronized with the viewing of peers' communication videos so that feedback could be marked to the relevant point on the video. Expert evaluation scores showed that students' communication performance, when involved in peer assessments, significantly improved. In the first round, the scores determined by the peers were not correlated with those marked by the experts. However, in the second round, both scores were significantly correlated, indicating that the online peer assessment could be perceived as a valid assessment method for nursing communication skills training. Moreover, the analysis of peer feedback also revealed that their communication became more patient-centered gradually due to the peer assessments. On the whole, the students were satisfied with the peer assessment activities and appreciated the contribution to their communication skills. Highlights: An online peer valuation was planned to train nursing students' communication skills. We examined the effects and the validity of the peer assessment. The online peer assessment could enhance students' communication performance. Students' communication assessment skills have promoted via online peer valuation. Students were satisfied with the peer assessment activities.